Ten-year inhospital mortality trends for patients with trauma in Japan: a multicentre observational study. Issue 2 (8th February 2018) - Nagata, Isao; Abe, Toshikazu; Uchida, Masatoshi; Saitoh, Daizoh; Tamiya, Nanako
Abstract : Objectives: Trauma is one of the main causes of death in Japan, and treatments and prognoses of these injuries are constantly changing. We therefore aimed to investigate a 10-year trend (2004–2013) in inhospital mortality among patients with trauma in Japan. Design: Multicentre observational study. Setting: Japanese nationwide trauma registry (the Japan Trauma Data Bank) data. Participants: All patients with trauma whose Injury Severity Score (ISS) were 3 and above, who were aged 15 years or older, and whose mechanisms of injury (MOI) were blunt and penetrating between 2004 and 2013 (n=90 833). Outcome measures: A 10-year trend in inhospital mortality. Results: Inhospital mortality for all patients with trauma significantly decreased over the study decade in our Cochran-Armitage test (P<0.001). Similarly, inhospital mortality for patients with ISS 16 or more and patients who scored 50% or better on the Trauma and Injury Severity Score (TRISS) probability of survival scale significantly decreased (P<0.001). In addition, the OR for inhospital mortality of these three patient groups decreased yearly after adjusting for age, gender, MOI, ISS, Glasgow Coma Scale, systolic blood pressure and respiratory rate on hospital arrival in multivariable logistic regression analyses. Furthermore, inhospital mortality for patient with blunt trauma significantly decreased in injury mechanism-stratified Mantel-extension testing (P<0.001). Finally, multivariable logistic regression analyses showed that the OR for inhospital mortality of patients with ISS 16 and over decreased each year after adding and adjusting for means of transportation and usage of whole-body CT. Conclusion: Inhospital mortality for patients with trauma in Japan significantly decreased during the study decade after adjusting for patient characteristics, injury severity and the response environment after injury.